KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS DENGUE FEVER AMONG PATIENTS IN HOSPITAL TAIPING - Mohammed Abdelfatah Alhoot; Mohammed Faez Baobaid; Anis Rageh Al-Maleki; Mohammed A. Abdelqader; Lavannya A/P Rangas Paran; Bavani A/P Kannaiah; Kavitha A/P Balasingam; Mathuri A/P Appanu; Paveetran A/L Bathmanathan; Murugan A/L Maniam (Malaysian Journal of Public Health Medicine, 2017)
Dengue fever is the most common vector-borne disease and major concern issues in Malaysia. Thus, the present study aimed to evaluate factors influencing knowledge, attitude, and practices regarding dengue fever among patients in Hospital Taiping. A total of 300 patients were incorporated into a descriptive, public based cross-sectional study. The questionnaires were formulated to include several questions on demographic data, knowledge, attitudes, and practices concerning dengue fever. Most of the respondents were from the age group of more than 35 (43.3%). The largest representations of the participants were Malay (59.3%), married (65.7%), SPM is the highest education level (53.3%), and 60.7% of the participants were conscious about dengue fever eruption. Television/radio was voted as the frequent source of information (97.3%). There is no significant relationship between knowledge score and socio-demographic factors. However, around 57.0% of the respondents believe that abdominal pain is not a symptom of dengue fever and 32% convinced that blood transfusion can transmit dengue. No significant correlation was found between attitude and practice score to socio-demographic characters. However, a good practice towards dengue fever is associated with good knowledge (65.4 %) nevertheless it did not influence their attitude. Moreover, the attitude seems to be poor regardless of knowledge level (44.0%). Therefore, more prevention practices to raise the awareness of population toward dengue fever such as health campaigns and health education in school level should be initiated. These activities will aid in fertilizing better attitude and prevention practice towards dengue fever and bring down its incidence in Malaysia.